2008
DOI: 10.1186/1753-2000-2-26
|View full text |Cite
|
Sign up to set email alerts
|

A three-country comparison of psychotropic medication prevalence in youth

Abstract: BackgroundThe study aims to compare cross-national prevalence of psychotropic medication use in youth.MethodsA population-based analysis of psychotropic medication use based on administrative claims data for the year 2000 was undertaken for insured enrollees from 3 countries in relation to age group (0–4, 5–9, 10–14, and 15–19), gender, drug subclass pattern and concomitant use. The data include insured youth aged 0–19 in the year 2000 from the Netherlands (n = 110,944), Germany (n = 356,520) and the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
120
4
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(139 citation statements)
references
References 36 publications
10
120
4
2
Order By: Relevance
“…In contrast to the findings of this study, SSRIs were the most frequently prescribed drugs in studies carried out in Asia, Europe, North America and India [3,14,15,21,[31][32][33][34] with decreased use of TCAs. Factors such as differences in culture, practice, promotional activity [32,35,36] and national income [37] contribute to these regional differences.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the findings of this study, SSRIs were the most frequently prescribed drugs in studies carried out in Asia, Europe, North America and India [3,14,15,21,[31][32][33][34] with decreased use of TCAs. Factors such as differences in culture, practice, promotional activity [32,35,36] and national income [37] contribute to these regional differences.…”
Section: Discussionmentioning
confidence: 99%
“…(Table 1). 9 They found relatively modest cross-national differences in the prevalence of total anti-psychotics (from 0.34 per 100 youth in Germany to 0.76 per 100 youth in the United States), but the proportion of AAPs in relation to total anti-psychotic use was much lower in Germany (5 per cent) than in the two comparator countries (48 per cent in the Netherlands and 66 per cent in the United States). The authors discussed a number of factors that might explain observed variations in psychotropic medication in young people in the three countries although they did not distinguish factors specifically related to AAP use.…”
Section: Atypical Anti-psychoticsmentioning
confidence: 99%
“…Indeed, most studies reviewed here pointed to differences in access to specialists as a likely driver of international variation in areas such as atypical anti-psychotics, 9 dementia, 14 15 and rheumatic arthritis. 18 For example, studies highlighted that there is great variation among European countries in whether or not GPs are authorised to initiate and/or continue dementia treatment initiated by specialists.…”
Section: Service Organisation Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] According to Canadian pharmacoepidemiologic data, antipsychotic medications have been prescribed for the treatment of attentiondeficit/hyperactivity disorder (17%), mood and conduct disorders (14%-16%) and psychosis (13%) in young people. 4 Currently, aripiprazole, a second-generation antipsychotic drug, is approved in Canada for the treatment of bipolar I disorder (manic or mixed episodes) in youth 13-17 years old and for schizophrenia in those 15-17 years old. In the United States, the Food and Drug Administration has approved a number of secondgeneration antipsychotic medications for the treatment of bipolar disorder, schizophrenia, and irritability (in the context of autism) in youth.…”
mentioning
confidence: 99%